The Transcription Factor SsSR Mediates Ergosterol Biosynthesis and Virulence in Sclerotinia sclerotiorum - Huihui Zhao; Xiaofan Liu; Jintao Jiang; Jiatao Xie; Yanping Fu; Yang Lin; Tao Chen; Bo Li; Xiao Yu; Xueqiong Xiao; Xueliang Lyu; Weidong Chen; et al. (Journal of Fungi, 2025)
Sclerotinia sclerotiorum, known as a typical necrotrophic pathogenic fungus, exhibits a complex pathogenic mechanism. Research on S. sclerotiorum has primarily focused on oxalic acid, pathogenicity-related enzymes, and secreted proteins. In this study, we identified a transcription factor, SsSR (S. sclerotiorum Sterol-Related transcription factor), which regulates S. sclerotiorum infection by modulating virulence through ergosterol biosynthesis. We characterized the transcriptional activity of SsSR and its downstream target gene, SsCYP51. SsSR undergoes phosphorylation induced by the host plant, subsequently regulating the expression of SsCYP51. The deletion of SsSR or SsCYP51 does not affect the growth or acid production of S. sclerotiorum, but it leads to a reduction in ergosterol, significantly diminishing virulence and impairing the stress tolerance of the hyphae. In summary, this study identifies a transcription factor, SsSR, that specifically regulates the virulence of S. sclerotiorum. SsSR upregulates the expression of SsCYP51 through phosphorylation during the infection phase, leading to the synthesis of ergosterol, which enhances hyphal stress tolerance and thereby promotes infection.